Hybrid Systems of Oleogels and Probiotic-Loaded Alginate Carriers for Potential Application in Cosmetics - Anna Łętocha; Małgorzata Miastkowska; Elżbieta Sikora; Alicja Michalczyk; Marta Liszka-Skoczylas; Mariusz Witczak (Molecules)
Oleogels (organogels) are systems resembling a solid substance based on the gelation of organic solvents (oil or non-polar liquid) through components of low molecular weight or oil-soluble polymers. Such compounds are organogelators that produce a thermoreversible three-dimensional gel network that captures liquid organic solvents. Oleogels based on natural oils are attracting more attention due to their numerous advantages, such as their unsaturated fatty acid contents, ease of preparation, and safety of use. As a result of the research, two oleogels were developed, into which freeze-dried alginate carriers with a probiotic, L. casei, were incorporated. Two techniques were used to produce probiotic-loaded capsules—extrusion and emulsification. Alginate beads obtained by the extrusion process have a size of approximately 1.2 mm, while much smaller microspheres were obtained using the emulsification technique, ranging in size from 8 to 17 µm. The trehalose was added as a cryoprotectant to improve the survival rate of probiotics in freeze-dried alginate carriers. The encapsulation efficiency for both of the methods applied, the emulsification and the extrusion technique, was high, with levels of 90% and 87%, respectively. The obtained results showed that the production method of probiotic-loaded microspheres influence the bacterial viability. The better strain survival in the developed systems was achieved in the case of microspheres produced by the emulsification (reduction in bacterial cell viability in the range of 1.98–3.97 log in silica oleogel and 2.15–3.81 log in sucragel oleogel after 7 and 30 days of storage) than by the extrusion technique (after a week and a month of oleogel storage, the decrease in cell viability was 2.52–4.52 log in silica oleogel and 2.48–4.44 log in sucragel oleogel).